THE EFFECT OF HARVEST PREMIUMS ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION OF OIL PALM HARVEST EMPLOYESS AT PT. SOCFINDO SEUNAGAN - Keumala Fadhiela ND; Abdul Muzammil; Anisah Nasution; Putri, Vidia Wirma (RADJA PUBLIKA, 2023)
Employee harvest premiums are one approach for oil palm enterprises to boost production. Premiums are believed to strengthen human resources and motivate workers. The purpose of this study is to investigate the impact of harvest premiums on the performance and work satisfaction of harvest personnel at the research location. This study was carried out at PT Socpindo Seunagan in Nagan Raya Regency. The research site was chosen on purpose, and the sampling strategy used in this study was proportional stratified random sampling, with 38 samples drawn from each afdeling. According to the study's findings, the harvest premium has a meaningful impact on performance (work quantity, work quality, and work attendance) and employee job satisfaction at PT Socpindo Seunagan.